An analysis of factors influencing the demand for community-based integrated health and social care in Southwestern China - Zheng, Hanzhi; Yang, Min; Zeng, Qin; Liao, Shujuan; Li, Ping (Frontiers in Public Health, 2025)
ObjectiveThis cross-sectional study investigates the demand for CB-IHSC among older adults in Chengdu and identifies the factors influencing this demand, thereby providing a reference for developing and optimizing such services.MethodsFrom August to December 2023, 511 eligible older adults residing in the central districts of Chengdu were selected through convenience sampling. Guided by the Andersen Health Service Utilization Behavior Model, the study categorized influencing factors into three dimensions: predisposing factors, enabling factors and need factors. Chi-square tests were first used to identify statistically significant variables within each dimension. These variables were then included in a binary logistic regression model to assess their association with service demand. Model calibration was assessed using the Hosmer–Lemeshow test.ResultsDemand for CB-IHSC was high (87.08%). Independent predictors included number of children (OR = 2.12), living with spouse (vs alone, Ref; OR = 0.48), lower income (OR = 0.40), convenient community medical access (OR = 1.75), children’s support (OR = 3.71), lower self-care ability (OR = 0.18), poorer self-rated health, and higher awareness. Policies should improve accessibility, financing, and public awareness to increase uptake.ConclusionTo support the sustainable development of CB-IHSC, Chengdu should continue strengthening capacity building in this sector. Efforts should be directed toward establishing diversified financing and support mechanisms, improving the accessibility and convenience of service delivery, and enhancing public awareness and education regarding CB-IHSC.